Clinical and Genetic Analysis of an Infertile Male with 46, XX/46, XY Chimerism. (10th December 2018) - Choi, Eun Jung; Kim, Sook Ryung; Kim, Young Joo; Kang, Soo Man; Kim, Gi Young; Kim, Jong Hyun; Lee, Young Jin
Abstract: The sex chromosome‐discordant chimerism 46, XX/46, XY is rarely found in humans with a phenotypically normal appearance, and this lack of phenotypic changes and the rarity of chimerism make it difficult to identify its exact incidence. Here, we report a case of this sex chromosome‐discordant chimerism diagnosed by cytogenic and molecular analyses of peripheral blood in a phenotypically normal male who was referred to our facility for infertility. Based on the karyotype, fluorescence in situ hybridisation (FISH) and short tandem repeat (STR) analyses, the type of this chimerism was determined to be tetragametic presenting four alleles at two loci on chromosomes 16 and 21.